Drought Risk Assessment by Applying Drought Hazard and Vulnerability Indices for Rainfed Wheat (Triticum aestivum L.) (Case study: North Khorasan and Razavi Khorasan) - H Latifi; S Khorramdel; A Koocheki; M Bannayan; M. R Farzaneh Belgredi (پژوهشهای زراعی ایران, 2025)
IntroductionThe assessment of risks in the agricultural sector serves as the foundation for developing risk management strategies. This is achieved through the analysis, identification, and prioritization of risks. It also acts as a tool to assist decision-makers in the agricultural sector to comprehend, confront, and manage risks, while identifying potential mitigation, transfer, and response mechanisms. Furthermore, it can be utilized to establish effective risk management strategies. There are several approaches to assess drought vulnerability and risk, with these two critical components being calculated using various indicators in different studies. The vulnerability index comprises exposure, sensitivity, and adaptive capacity as its major components. These elements significantly influence studies that utilize vulnerability indices to investigate the impacts of climate change and natural disasters. Therefore, the primary objective of this study was to evaluate the risks associated with wheat production, with a specific focus on vulnerability indices.Materials and MethodsThis study investigated drought risk, drought vulnerability, and drought hazard in Northeast Iran (North Khorasan and Razavi Khorasan provinces) on rainfed wheat production during 2009-2018. Exposure, sensitivity, and adaptive capacity determine the agricultural drought vulnerability. Two parameters of soil water holding capacity and level of mechanization were considered effective adaptive capacity factors in reducing the negative effects of drought on rainfed wheat production. The Combined Compromise Solution (CoCoSo) method was used to solve the multi-criteria agricultural drought vulnerability index problem.Results and DiscussionResults showed that among the 12 counties in Khorasan provinces, three are exposed to low drought vulnerability, 3 to moderate drought vulnerability, and 6 are highly or very high vulnerable. Counties with less drought vulnerability have a high score in terms of the adaptive capacity index, attributed to the high water-holding capacity of the soil in these areas. Drought hazard is primarily influenced by the weight and severity of SPI, with regions in the very high drought hazard classes mostly located in North Khorasan. In general, rainfed wheat is produced with low and medium risk in 11 counties of North Khorasan and Razavi Khorasan provinces. The lowest risk of dry wheat production was in Farouj (located in North Khorasan), and the highest risk is related to Sarakhs (in Razavi Khorasan).ConclusionRisk, as a fundamental factor of food insecurity, traps millions of households in poverty each year. The rising frequency and intensity of climate-related risks, driven by climate change, exacerbate cycles of damage and recovery while amplifying uncertainty. Arid regions face many of the same risks as other areas; however, challenges such as water scarcity, drought, desertification, and extreme temperatures are more acute in these regions, with far-reaching adverse effects. In arid and semi-arid regions, many production systems may disappear in the future. Therefore, risk assessment within the agricultural sector becomes crucial to quantify both the quantity and quality of risk while examining the potential consequences of a potential incident. This approach is critical for understanding, confronting, and identifying appropriate strategies to mitigate, transfer, and manage these risks. It provides valuable insights to decision-makers in the agricultural sector and serves as a basis for developing appropriate risk management solutions. Considering the undeniable impact of climate change on agriculture in arid and semi-arid regions, the dependence on available soil water and level of mechanization, components of the adaptive capacity index in this study, may no longer be sufficient. Hence, it is essential to explore alternative methods, including crop improvement, to reduce vulnerability to drought. In this respect, technologies such as soil cover applications and nutrient management can significantly contribute to reducing vulnerability to drought.AcknowledgmentThis project related to the Ph.D. thesis was financially supported by the Vice President for Research of the Faculty of Agriculture at Ferdowsi University of Mashhad.